Hitaveita (District Heating) in Akureyri - Flovenz, Olafur G. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1996)
Akureyri is a town of 15,000 inhabitants located in central N-Iceland. It has been heated by geothermal energy since the end of the seventies. Prior to that, it was partly heated by electricity, but mainly with oil burners, located within individual buildings. During the period 1928-1970, several attempts were made to exploit known hot spring areas in the vicinity of Akureyri. These attempts failed. Following the jump in energy price during the oil crisis of 1973, considerable effort was put into further exploration